Control Strategy of Cascade STATCOM based on Internal Model Theory - Zhenglong Xia; Liping Shi; Li Qianqian (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Internal model control (IMC) method enables the system to be of good dynamic and steady performance, which is simple, and is easy to be implemented. In allusion to the cascade STATCOM feature of high order, instability, multi-variable, non-linearity and tight coupling, the mathematical model of cascade STATCOM in d-q-0 coordinates was deduced. Decoupling model of cascade STATCOM was given by Internal Model Control principle, computer simulation and experiment results were also given. Results show that with IMC, 3-phase currents control method of cascade STATCOM has good tracking performance and control precision both in a-b-c coordinates and in d-q-0 coordinates, and also achieves excellent current compensation results. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4452